Male Infertility: Causes and Optimal Evaluation - Hossain, Md Abul; Naser, Md Fazal; Azam, Md Shafiqul; Islam, Md Waliul; Biswas, Nitai Pada; Bhuiyan, AKM Musa; Faruque, Mohammad Salahuddin (Bangladesh Journal of Urology, 2020)
Objective: To find out the optimum evaluation tools for male infertility. Methods: Hinari database were searched for articles related to male infertility for review to find out how a male infertile patient can be evaluated optimally.EUA guidelines on Male Infertility and AUA best practice statement on Optimal Evaluation of the Infertile Male updated on 2010 were also considered for review. Results: Initially thirty five articles were obtained and finally twenty eight articles were considered for review. Some cross references were considered to be cited in the reference section. We have mentioned in this review the evaluation tools those are necessary for male factor infertility at the optimum. Conclusion : As male infertility problem are increasing so optimum evaluation should be carried out to diagnose every possible underlying cause. Bangladesh Journal of Urology, Vol. 19, No. 1, Jan 2016 p.43-48